Ventriculo-atrial shunt by percutaneous approach. Technical analysis and case report - Ortiz Vica, A. Emanuel; Saravia Toledo, Alejandro; Morsucci, Edgardo; S. Jaikin, Mario; A. Petre, César (Revista Argentina de Neurocirugía, 2020)
Introduction: Cerebrospinal fluid drainage surgery to the venous system is used as a treatment for hydrocephalus in cases of peritoneal dysfunction. We weigh the percutaneous puncture to insert the distal catheter and use the necessary tools for its correct atrial location.Materials and methods: The study period runs from January 2013 to April 2019. The work includes a total of 45 patients, 24 females and 21 males. The age range is 6 months to 18 years. The modified “Seldinger” technique with ultrasound assistance and intraoperative radioscopic control was used to introduce the catheter distal to the venous system. The minimum follow-up was 1 year at the Hospital de Niños "Ricardo Gutiérrez" in CABA.Results: The causes of hydrocephalus were: myelomeningocele, 17 cases (38 %); congenital, 9 (20 %); tumors, 7 (16 %); post-infective, 6 (14 %); post-hemorrhagic: 5 (11 %); choroid plexus hyperplasia: 1 (2 %). Proximal obstruction occurred in 7 cases (15 %), infections in 5 (11 %), distal dysfunction 4 (8 %) and there were 1 patient (2 %) which exhibited distal venous migration of the intravascular segment. The right internal jugular vein was the site of choice for puncture, 37 cases (82 %); there was almost the same distribution in the location of the frontal and occipital-atrial proximal segments, 23 (51 %) 22 (49 %) respectively; fixed medium pressure valves were most frequently used, total of 40 (89 %). There were no cases of perioperative mortality. Surgical indication involved peritoneal engagement in all cases.Conclusion: Atrial ventricle shunt surgery by percutaneous puncture is a safe technique, not free of complications, which decrease with the correct order of your steps and complement radiology and intraoperative ultrasound.
Keywords: Surgical Technique; Hydrocephalus; Percutaneous Atrial Ventricular Shunt; Complications